Evaluation of Pre-disaster Planning of Bengawan Solo River Flood Bojonegoro Regency Year 2014 - Enov Sayu Mimanggar Mirahesti (Universitas Airlangga, 2016)
In early 2014, floods ranked first in natural disasters with an incidence of 69 cases in Bojonegoro District. Rapid Health Assessment activity in Bojonegoro District were not optimal so that pre-disaster activities needed to be evaluated. The purpose of this study was to evaluate the activities of flood pre-disaster planning in Bojonegoro District in 2014. Data collection was carried out using interview techniques and document studies. Data analysis was performed descriptively. The results showed that based on the input component, the Standard Operational Procedure (SOP) and facilities had met the standards, while the implementing staff, types of data, and funds still did not meet the standards. Based on the process components, contingency planning has been carried out in accordance with the standards. Geomedical mapping was not carried out and no social and economic identification was carried out in the planning process of prevention, mitigation, and disaster preparedness activities. Based on the output component, the health department already has a contingency plan but does not have a geomedical map and a plan for prevention, mitigation, and disaster preparedness activities. The conclusion that can be drawn is the pre-disaster planning activities of the Bojonegoro District Health Office is still not good. It is recommended to control SOP, add executing staff, complete types of data, allocate ready-made funds, prepare budget plans, provide special vehicles, conduct social and economic identification, provide training to officers, and make an outline of geomedical maps and plans for prevention efforts, mitigation, and disaster preparedness.